Early Diagnosis of Acute Kidney Injury during Open Heart Surgery under Extracorporeal Circulation - E. A. Tabakyan; S. A. Partigulov; M. G., Lepilin; I. V. Burmistrova; V. D. Vodyasov; T. I. Kotkina; V. N. Titov (Общая реаниматология, 2013)
Objective: to analyze the informative value of new methods for the early diagnosis of acute kidney injury (AKI) to determine treatment policy after heart surgery under extracorporeal circulation (EC). Subjects and methods. Patients of both sexes were examined before and after heart surgery under EC. A perfusion index of 2.5±0.4 l/min/m2, moderate hypothermia, and a mean blood pressure of 60—100 mm Hg were maintained throughout EC. Urine samples were taken 4—6 and 16—18 hours after termination of EC and centrifuged. Urinary neutrophil gelatinase associated lipocalin (NGAL) was determined using an Abbott Architect i1000sr analyzer. The cutoff level proposed by the Abbott Diagnostics was 132 ng/ml. NonResults. Two groups were formed. Group 1 included 14 patients with AKI according to the 2004 RIFLE classification. Stage 1 AKI was seen in 5 cases; there was no disease progression or urinary NGAL elevation. Four to six hours after EC, 8 of 9 patients with Stages 2—3 AKI had a urinary NGAL level of 200 ng/ml. Two patients required renal replacement therapy (RRT), their renal function recovery was observed. Other two patients died from respiratory and cardiac failure. Group 2 comprised 61 patients without AKI: in 59 and 2 patients, urinary NGAL levels were lower and higher than the accepted cutoff levels, respectively. No deaths were observed. AKI developed in patients who had more prolonged EC, transverse aortic ligation, low hemoglobin levels and received more doses of donor blood. In Stages 1—3 AKI, the sensitivity was 57.1% (95% confidence interval (CI), 28.9—82.2) and specificity was 96.7% (95% CI, 88.6—99.5); in Stages 2—3 AKI, these were 88.9% (95% CI, 51.7—98.2) and 97% (95% CI, 89.5—99.5), respectively. Conclusion. Urinary NGAL levels should be determined by using the laboratory platforms 4—6 hours after long EC, as well as aortic ligation, and transfusion of two or more blood doses. Elevated urinary NGAL levels are highly sensitive to Stages 2—3 AKI and useful in assessing indications by the beginning of RRT. Key words: cardiac surgery under extracorporeal circulation, acute kidney injury, urinary NGAL, urinary albumin to creatinine ratio.